Analisis Pengaruh CAR, NPL, LDR dan NIM Terhadap Profitabilitas Perbankan di Indonesia (Literature Review Manajemen Keuangan Perusahaan) - Maria Veronika Dora Wesso; Henny A Manafe; Stanis Man (Dinasti Review, 2022)
Abstract: Previous studies that have a discussion theme have an important role in strengthening the theory as well as the interrelationships and influences between variables. This study reviews CAR, NPL, LDR and NIM in influencing banking profitability in Indonesia. This study the researchers wrote with the intention of determining the hypothesis between variables in the next study. The results of this review are: 1) Capital adequacy ratio (CAR) has a positive or significant impact on profitability (ROA); 2) Nonperforming loans (NPL) have a positive or significant impact on profitability (ROA); 3) Loan to deposit ratio (LDR) has a positive or significant impact on profitability (ROA); 4) Net Interest Margin (NIM) has a positive or significant impact on profitability (ROA); 5) CAR, NPL, LDR and NIM simultaneously have a positive or significant impact on the profitability of banks in Indonesia. Abstrak: Kajian sebelumnya yang memiliki tema pembahasan memiliki peranan penting demi menguatkan teori maupun keterkaitan dan pengaruh antarvariabel. Kajian ini mengulas CAR, NPL, LDR dan NIM dalam memengaruhi profitabilitas perbankan di Indonesia. Kajian ini peneliti tulis dengan maksud menentukan hipotesis antarvariabel pada kajian berikutnya. Hasil dari ulasan ini ialah: 1) Capital adequacy ratio (CAR) memengaruhi positif maupun bermakna pada profitabilitas (ROA); 2) Nonperforming loan (NPL) memengaruhi positif maupun bermakna pada profitabilitas (ROA); 3) Loan to deposit ratio (LDR) memengaruhi positif maupun bermakna pada profitabilitas (ROA); 4) Net Interest Margin (NIM) memengaruhi positif maupun bermakna pada profitabilitas (ROA); 5) CAR, NPL, LDR dan NIM secara bersamaan memengaruhi positif maupun bermakna pada profitabilitas perbankan di Indonesia.